J-integral analysis: An EDXD and DIC comparative study for a fatigue crack. (May 2020) - Koko, A.; Earp, P.; Wigger, T.; Tong, J.; Marrow, T.J.
Highlights: J-integral analyses for deformation fields obtained using EDXD and DIC. SIF calculation with no knowledge of the specimen geometry, crack length or applied loads. Crack tip tracking using phase congruency and FWHM with DIC and EDXD data, respectively. Abstract: Synchrotron Energy Dispersive X-ray Diffraction (EDXD) and Digital Image Correlation (DIC) have been applied to map simultaneously the 2D elastic strain and displacement fields of a propagating fatigue crack in the HAZ of a welded Cr2Ni4MoV bainitic steel. The position of the crack tip was tracked via a phase congruency analysis of the displacement field, and also by detection of its cyclic plastic zone. Both types of full field data provided independent inputs to finite element/J-integral analyses that directly quantified the elastic cyclic stress intensity factor range applied to the crack. No knowledge was required of the specimen geometry, crack length or applied loads. The agreement between the two analyses in this controlled study shows that strain mapping by synchrotron EDXD can provide a reliable method to study the crack fields in more complex problems, such as interactions between crack closure, residual stresses and applied loading.